2007
DOI: 10.1042/ba20060103
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytochrome c detection using a cytochrome c oxidase biosensor

Abstract: Within the last ten years it has emerged that the release of cytochrome c plays a critical role in the important process of programmed cell death. It has also been shown that this protein is released into the circulating blood following MIs (myocardial infarctions). Methods for the detection of this protein have therefore become important. The enzyme cytochrome c oxidase is specific for cytochrome c. Bovine cytochrome c oxidase was successfully immobilized in a didodecyldimethylammonium bromide vesicular syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…To that end, the few existing reports have mainly focused on detection of cyt c in biological samples, since its presence in blood can be indicative of several pathologies related to damaged mitochondria, such as apoptotic cell death, myocardial infarctions, and a number of neurological diseases [224]. The reported cyt c sensing applications include those that rely on (i) immobilization of CcO onto Au electrode-supported lipid bilayer membranes; the oxidase-modified electrode operates as an amperometric biosensor capable of detection of reduced cyt c with detection limit of 0.1 µM [127], (ii) casting of CcO-didodecyldimethylammonium bromide (DDAB) vesicle films onto Au electrodes for detection of ferric cyt c in human blood serum [126], and (iii) CcO deposited over Au electrodes modified with NiONPs, CNTs and a conducting PANI polymer (NiONPs/cMWCNT/PANI hybrid) [225]. The amperometric biosensors for cyt c based on these hybrid films were investigated by CV, electrochemical impedance spectroscopy (EIS), SEM, and FTIR [225], revealing a linear range between 1 × 10 −6 and 0.1 µM, a superior detection limit in different serum samples (5 × 10 −6 µM) and sensitivity of 3.7 × 10 6 A M −1 cm −2 [225].…”
Section: Cytochrome C Oxidasesmentioning
confidence: 99%
“…To that end, the few existing reports have mainly focused on detection of cyt c in biological samples, since its presence in blood can be indicative of several pathologies related to damaged mitochondria, such as apoptotic cell death, myocardial infarctions, and a number of neurological diseases [224]. The reported cyt c sensing applications include those that rely on (i) immobilization of CcO onto Au electrode-supported lipid bilayer membranes; the oxidase-modified electrode operates as an amperometric biosensor capable of detection of reduced cyt c with detection limit of 0.1 µM [127], (ii) casting of CcO-didodecyldimethylammonium bromide (DDAB) vesicle films onto Au electrodes for detection of ferric cyt c in human blood serum [126], and (iii) CcO deposited over Au electrodes modified with NiONPs, CNTs and a conducting PANI polymer (NiONPs/cMWCNT/PANI hybrid) [225]. The amperometric biosensors for cyt c based on these hybrid films were investigated by CV, electrochemical impedance spectroscopy (EIS), SEM, and FTIR [225], revealing a linear range between 1 × 10 −6 and 0.1 µM, a superior detection limit in different serum samples (5 × 10 −6 µM) and sensitivity of 3.7 × 10 6 A M −1 cm −2 [225].…”
Section: Cytochrome C Oxidasesmentioning
confidence: 99%
“…9). Ashe et al, have designed a CcO based biosensor for the detection of cyt c levels in serum (Ashe et al, 2007). For example, a study by Cullison and Hawkridge showed that CcO can measure either both oxidized or reduced cyt c when an appropriate voltage is applied (Cullison et al, 1994).…”
Section: Cytochrome C Oxidase Based Biosensormentioning
confidence: 99%
“…However, the rate of reduction of oxidized form of cyt c by CcO was less than the oxidation of reduced form of cyt c. Ashe et al, also used to detect oxidized form of cyt c in serum samples using CcO to evaluate its possible application in detecting early myocardial infarctions (Ashe et al, 2007).…”
Section: Cytochrome C Oxidase Based Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, electrochemical biosensors have gained considerable attention and evolved as an alternative technique for the measurement of cyt c [11][12][13]. These biosensors either based on electrostatic interaction or cyt c oxidase, lacking specificity or measure only the non-apoptotic form of cyt c (Fe(II)) and hence are not suitable for the measurement of apoptosis.…”
Section: Introductionmentioning
confidence: 99%